Análise do desconforto acústico proveniente das fontes de ruídos em escritórios de plano aberto (open-plan offices): uma aplicação prática de modelo proposto - Dias, Márcio Carlos Ferreira (2012)
This study comprises an analytical approach on the acoustic discomfort in open plan offices (open-plan offices), whose layout with partitions, widely used, does not provide adequate privacy. Given the discomfort acoustic open-plan offices, this study aims to determine what are the sources of noise and how uncomfortable they are to their users. The noise in this environment comes from several sources: conversation, printers, air conditioning outlets, phone ringing etc.. Through the literature review was possible to verify the existence of various resources to mitigate these noise: acoustic lining, partitions, noise masking, among others. However, the study's objectives were achieved through the application of a research plan, developed in this paper, which conducted the study in a structured way, in a format able to bring results amenable to comparison with other studies. One result has been shown that human speech is the most disturbing acoustic (30%), followed by the ringing of the telephone (25%). It was possible to determine how much each source of noise which causes discomfort and other labor disturbances are posed by the impact of noise in this environment